The impact of body mass index on laboratory, clinical outcomes and treatment costs in assisted reproduction: a retrospective cohort study - Victoria Campos Dornelles; Marta Ribeiro Hentschke; Mariangela Badalotti; Isadora Badalotti Telöken; Vanessa Devens Trindade; Bibiana Cunegatto; Natália Fontoura de Vasconcelos; Bartira Ercília Pinheiro da Costa; Alvaro Petracco; Alexandre Vontobel Padoin (BMC, 2022)
Abstract Background The aim of this study was to evaluate the influence of the body mass index (BMI) on laboratory, clinical outcomes and treatment costs of assisted reproduction, as there are still controversial and inconclusive studies on this subject. Methods This research was retrospective cohort study, including women undergoing assisted reproduction in a Reproductive Medicine Center between 2013 and 2020. The participants were divided into groups according to BMI (kg/m2): Group 1 < 25; Group 2, 25-29.9 and Group 3, ≥ 30. A total of 1753 in vitro fertilization (IVF) fresh embryo transfer (ET) cycles were included for assisted reproduction outcomes analysis and 1869 IVF-ET plus frozen embryo transfer (FET) for cumulative pregnancy analysis. Results As higher the BMI, higher was the proportion of canceled IVF cycles (G1 (6.9%) vs. G2 (7.8%) vs. G3 (10.4%), p = 0.002) and gonadotropin's total dose (IU) and treatment costs (G1 (1685 ± 595, U$ 683,02) vs. G2 (1779 ± 610, U$ 721,13) vs. G3 (1805 ± 563, U$ 764,09), p = 0.001). A greater number of mature oocytes was observed in G1 and G2 (6 [6.4-7.0] vs. 6 [5.6-6.6] vs. 4 [4.6-6.7], p = 0.011), which was not found in oocyte maturity rate (p = 0.877). A significant linear tendency (p = 0.042) was found in cumulative pregnancy rates, pointing to worse clinical outcomes in overweight and obese patients. Conclusion These findings highlight the importance of considering the higher treatment costs for these patients, beyond all the well-known risks regarding weight excess, fertility, and pregnancy, before starting IVF treatments.